Gas diffusion cathode for anion exchange membrane water electrolysis hydrogen production as well as preparation and application of gas diffusion cathode

By using nickel-based non-precious metal powders and alloys as catalytic active components, combined with carbon-based conductive agents and binders such as polytetrafluoroethylene, a gas diffusion cathode with a porous composite structure was prepared, which solved the problems of high cost of precious metal catalysts and insufficient current density in the prior art, and achieved efficient and low-cost hydroelectric hydrogen production effect.

CN119736654APending Publication Date: 2025-04-01SHANGHAI JIAOTONG UNIV

Patent Information

Application Number
CN202411902016.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing gas diffusion cathode used for hydrogen production by water electrolysis of anion exchange membranes mainly relies on precious metal catalysts, resulting in high costs and current density that needs to be improved.

Method used

Nickel-based non-noble metal powders, alloys or their derivatives are used as catalytically active components, combined with carbon-based conductive agents and binders such as polytetrafluoroethylene, to prepare a gas diffusion cathode through a deposition method to form a porous composite structure to improve electrode performance.

Benefits of technology

It significantly reduces the cost of the catalyst, improves the current density and stability, and realizes an efficient hydroelectric hydrogen production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736654A_ABST
    Figure CN119736654A_ABST
Patent Text Reader

Abstract

The invention relates to a gas diffusion cathode for anion exchange membrane water electrolysis hydrogen production and a preparation method of the gas diffusion cathode. The gas diffusion cathode is composed of a hydrophobic conductive substrate such as carbon paper or carbon cloth and the like and a catalytic layer, and the catalytic layer takes nickel-based non-noble metal powder and at least one of alloys or derivatives of the nickel-based non-noble metal powder and the alloys as catalytic active components. One or more of carbon powder, carbon nanotubes, carbon nanofibers, graphene, nano graphite powder and the like are used as conductive agents, and polytetrafluoroethylene, polyvinylidene fluoride or perfluorosulfonic acid resin is used as binding agents, so that the gas diffusion cathode is formed. According to the gas diffusion cathode for anion exchange membrane water electrolysis hydrogen production, nickel-based non-noble metal active components are deposited on a conductive substrate of a porous composite structure, the preparation process is simple, an electrode with a uniform catalyst can be obtained, and compared with the similar technology, the gas diffusion cathode has the obvious advantages of high catalyst utilization rate and high current density; the cathode is applied to various water electrolysis electrochemical reduction reactors or electrolytic tanks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of gas diffusion electrodes, and specifically relates to a cathode gas diffusion cathode for anion exchange membrane water electrolysis to produce hydrogen and a preparation method thereof, and more particularly to a gas diffusion cathode for water electrolysis cathode reduction, which has a porous composite structure conductive substrate deposited with nickel-based non-precious powder and alloys or their derivatives as catalytic active components and a preparation method thereof. Background Art

[0002] Environmental issues caused by the uncontrolled consumption of fossil fuels have triggered intensive research on clean energy technologies. Hydrogen is widely considered to be one of the most promising candidates to replace traditional fossil fuels due to its high energy density and environmental friendliness. This is consistent with the recent need to ensure sustainable development. Along with renewable energy, water electrolysis is considered a promising system for achieving industrial hydrogen production.

[0003] Alkaline water electrolysis is advantageous in using earth-abundant elements and their compounds as electrocatalysts, and anion exchange membrane water electrolyzer (AEMWE) offers advantages such as lower ohmic resistance, lower gas permeation, and pressurized operation over conventional systems using bulk electrolytes and membrane separators. However, its insufficient performance and efficiency remain a challenge for economical hydrogen production.

[0004] The development of high-performance electrodes is essential to achieve economical hydrogen production using AEMWE technology. Among the metals that are abundant on Earth, recent studies have shown that Ni and Co are key elements for catalyzing HER in alkaline electrolytes because they have moderate hydrogen binding energies and can provide OH - and H ads The intermediates provide suitable adsorption. Previous studies reported the complementary role of bimetallic Ni-Co in enhancing the HER activity in alkaline electrolytes according to their composition. However, their catalytic activity is still unsatisfactory compared with Pt metal, indicating that further modification is required to promote its Gibbs free energy close to zero, as in the case of Pt. Therefore, some studies have been conducted by alloying with other elements, such as Ni-Co, Ni-Cu, Ni-La, etc.

[0005] These compounds exhibit excellent electrocatalytic activity for HER. Therefore, these electrocatalysts were prepared directly on the substrate by a deposition method, which can provide a fast and cost-effective process at room temperature and ambient pressure. By changing the deposition method, the morphology and composition of the catalyst can be easily controlled, which can significantly affect the HER catalytic activity. In addition, it can promote the acceleration of electron transfer through the contact between the catalyst and the substrate.

[0006] In summary, in current literature reports, gas diffusion cathodes used for anion exchange membrane water electrolysis are mainly based on electrodes of precious metal catalysts such as Pt, which are relatively expensive and the current density needs to be further improved. Summary of the invention

[0007] In view of the deficiencies in the prior art, the present invention relates to a gas diffusion cathode for anion exchange membrane water electrolysis to produce hydrogen and a preparation method thereof.

[0008] The objective of the present invention is achieved through the following technical solutions:

[0009] The present invention provides a catalytic layer of a gas diffusion cathode for anion exchange membrane water electrolysis to produce hydrogen, comprising a catalytically active component, a conductive agent, and a binder; the mass ratio of the catalytically active component to the conductive agent is 1:5 to 5:1; the catalytically active component is selected from at least one of nickel-based non-precious powders and alloys or their derivatives.

[0010] Preferably, the nickel-based non-precious metal powder and alloy are selected from one or more elements of NixMy (M = Fe, Co, Al, Cr, Mo, Mg, Mn, Zn, Sn, La, Cu, FeCo, MoCo, one or more, x = 0.2-0.9 (preferably 0.25-0.85, more preferably 0.50-0.70), y = 0.8-0.1 (preferably 0.75-0.15, more preferably 0.40-0.20));

[0011] Preferably, the conductive agent is selected from one or more of carbon powder, carbon nanotubes, carbon nanofibers, graphene, and nanographite powder.

[0012] Preferably, the binder is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride or perfluorosulfonic acid resin.

[0013] Preferably, the mass ratio of the catalytically active component to the conductive agent is 1:7 to 7:1.

[0014] Preferably, the mass of the binder is 10% to 40% of the total mass of the catalyst layer.

[0015] The present invention also provides a method for preparing the above-mentioned catalyst layer, comprising the following steps:

[0016] a) mixing a catalytically active component, a conductive agent and a binder to obtain a solid powder mixture;

[0017] b) adding a dispersant to the solid powder mixture and stirring with ultrasonic waves for 3 to 100 minutes to obtain a catalyst layer slurry;

[0018] c) coating the catalyst layer slurry onto a substrate and drying the catalytic layer.

[0019] Preferably, in step b), the mass ratio of the solid powder mixture to the dispersant is 1:1 to 200:1; the dispersant is selected from ultrapure water, anhydrous ethanol, isopropanol or n-butanol;

[0020] In step d), the coating method is selected from any one of electrodeposition, direct deposition, air spraying, electrostatic spraying, ultrasonic spraying, sputtering, doctor blade coating, screen printing and roller pressing.

[0021] The present invention also provides a gas diffusion cathode for anion exchange membrane water electrolysis to produce hydrogen, comprising a hydrophobic conductive porous substrate and the above-mentioned catalyst layer.

[0022] Preferably, the conductive porous substrate is a composite structure obtained by adding a surface smoothing layer to one or more of carbon paper, carbon cloth, porous titanium, nickel foam, zinc foam, and nickel-iron foam.

[0023] Preferably, the loading amount of the catalytically active component in the gas diffusion cathode is 2 mg cm -2 ~8mg cm -2 The more preferred loading amount of the catalytically active component is 4 mg cm -2 ~6mg cm -2 .

[0024] The present invention also provides a method for preparing a gas diffusion cathode for anion exchange membrane water electrolysis to produce hydrogen, comprising the following steps:

[0025] a1) mixing the catalytically active component, the conductive agent and the binder to obtain a solid powder mixture;

[0026] b1) adding a dispersant to the solid powder mixture and stirring with ultrasonic waves for 3 to 100 minutes to obtain a catalyst layer slurry;

[0027] c1) The catalyst slurry is coated onto a hydrophobic conductive porous substrate, and then dried at 60-80° C. for 1-12 h to obtain a gas diffusion cathode.

[0028] Preferably, in step b1), the mass ratio of the solid powder mixture to the dispersant is 1:1 to 200:1;

[0029] In step d1), the coating method is selected from any one of electrodeposition, direct deposition, air spraying, electrostatic spraying, ultrasonic spraying, sputtering, doctor blade coating, screen printing and roller pressing.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The present invention proposes a gas diffusion cathode for anion exchange membrane water electrolysis to produce hydrogen and a preparation method thereof. Compared with the prior art, the cost can be greatly reduced due to the use of non-precious metal materials as catalysts. On the other hand, in view of the problem of poor conductivity of the non-precious metal catalysts used, it is proposed to use conductive materials such as carbon powder, carbon nanotubes, carbon nanofibers, graphene, nanographite powder, etc. to construct an electron channel, and use one or more of polytetrafluoroethylene, polyvinylidene fluoride or perfluorosulfonic acid resin as a binder to achieve electrode formation while constructing a gas and liquid transmission channel in the electrode, thereby effectively improving the current density and stability of water electrolysis using the gas diffusion cathode.

[0032] 2. The gas diffusion cathode for anion exchange membrane water electrolysis to produce hydrogen proposed in the present invention uses non-precious metals as active components and a conductive porous composite material as a substrate. A gas diffusion cathode with a nickel-based catalyst deposited on the substrate is obtained by a deposition method. Compared with similar technologies, it has obvious advantages of high catalyst utilization, high current density and high stability.

[0033] 3. The gas diffusion cathode for anion exchange membrane water electrolysis to produce hydrogen proposed in the present invention uses non-precious metals as active components, has a simple electrode preparation process and can be scaled up, and has obvious advantages over similar technologies in terms of high catalyst utilization, high operating current density and high stability, and can be used as a cathode in various water electrolysis electrochemical reduction reactors or electrolytic cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0035] Figure 1 Schematic diagram of the electrolytic cell structure (where the catalytic layers of the cathode and anode are placed closely to the anion exchange membrane);

[0036] Figure 2 It is a schematic diagram of electrolytic cell testing;

[0037] Figure 3 The current density of hydrogen production by water electrolysis at different electrolytic cell voltages for the non-precious metal gas diffusion cathode and the precious metal cathode obtained in the examples. DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0039] The following embodiment provides a catalytic layer of a gas diffusion cathode for anion exchange membrane water electrolysis to produce hydrogen, comprising a catalytically active component, a conductive agent, and a binder; the mass ratio of the catalytically active component to the conductive agent is 1:7 to 7:1; the catalytically active component is selected from at least one of nickel-based non-precious metal powders and alloys or their derivatives.

[0040] The nickel-based non-precious metal powder and alloy are selected from one or more elements of NixMy (M = one or more of Fe, Co, Al, Cr, Mo, Mg, Mn, Zn, Sn, La, Cu, FeCo, MoCo, x = 0.2-0.9 (preferably 0.25-0.85, more preferably 0.50-0.70), y = 0.8-0.1 (preferably 0.75-0.15, more preferably 0.40-0.20));

[0041] The conductive agent is selected from one or more of carbon powder, carbon nanotubes, carbon nanofibers, graphene, and nanographite powder.

[0042] The binder is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride or perfluorosulfonic acid resin.

[0043] The mass ratio of the catalytically active component to the conductive agent is 1:7 to 7:1.

[0044] The mass of the binder is 10% to 40% of the total mass of the catalytic layer.

[0045] The method for preparing the catalytic layer comprises the following steps:

[0046] a) mixing a catalytically active component, a conductive agent and a binder to obtain a solid powder mixture;

[0047] b) adding a dispersant to the solid powder mixture and stirring with ultrasonic waves for 3 to 100 minutes to obtain a catalyst layer slurry;

[0048] c) coating the catalyst layer slurry onto a substrate and drying the catalytic layer.

[0049] In step b), the mass ratio of the solid powder mixture to the dispersant is 1:1 to 200:1; the dispersant is selected from anhydrous ethanol;

[0050] In step d), the coating method is selected from any one of electrodeposition, direct deposition, air spraying, electrostatic spraying, ultrasonic spraying, sputtering, doctor blade coating, screen printing and roller pressing.

[0051] The following embodiment also provides a gas diffusion cathode for anion exchange membrane water electrolysis to produce hydrogen, comprising a hydrophobic conductive porous substrate and the aforementioned catalyst layer.

[0052] The conductive porous substrate is a composite structure obtained by adding a surface smoothing layer to one or more of carbon paper, carbon cloth, porous titanium, foamed nickel, foamed zinc, and foamed iron nickel.

[0053] The gas diffusion cathode has a catalytically active component loading of 2 mg cm -2 ~8mg cm -2 The more preferred loading amount of the catalytically active component is 4 mg cm -2 ~6mg cm -2 .

[0054] The method for preparing a gas diffusion cathode for anion exchange membrane water electrolysis to produce hydrogen comprises the following steps:

[0055] a1) mixing the catalytically active component, the conductive agent and the binder to obtain a solid powder mixture;

[0056] b1) adding a dispersant to the solid powder mixture and stirring with ultrasonic waves for 3 to 100 minutes to obtain a catalyst layer slurry;

[0057] c1) The catalyst slurry is coated onto a hydrophobic conductive porous substrate, and then dried at 30-90° C. for 2-8 h to obtain a gas diffusion cathode.

[0058] In step b1), the mass ratio of the solid powder mixture to the dispersant is 1:1 to 200:1;

[0059] In step d1), the coating method is selected from any one of electrodeposition, direct deposition, air spraying, electrostatic spraying, ultrasonic spraying, sputtering, doctor blade coating, screen printing and roller pressing.

[0060] Under the above-mentioned parameter conditions, the gas diffusion cathode for producing hydrogen by anionic membrane water electrolysis according to the present invention can be prepared.

[0061] Example 1

[0062] A gas diffusion cathode for anion membrane water electrolysis to produce hydrogen and a preparation method thereof, the steps are as follows:

[0063] 1) 20 mg Ni 0.5 La 0.5 (Shanghai Hydrogen Luan Technology Co., Ltd., NiLa, powder particle size <50nm, the following table represents the atomic number ratio of the corresponding metal in the alloy, with the total number of atoms in the alloy as 1), 20mg nano graphite powder (powder particle size <50nm) and 100mg polytetrafluoroethylene (5wt%) are evenly mixed, polytetrafluoroethylene accounts for Ni 0.5 La 0.5and 11.1% of the total mass of nano-graphene powder and polytetrafluoroethylene, then 35 mg of anhydrous ethanol was added to the solid powder mixture, and ultrasonically stirred at room temperature for 60 min to obtain a catalyst layer slurry.

[0064] 2) The catalyst layer slurry obtained above was ultrasonically sprayed onto one side of the surface of the sheet carbon paper (length * width * thickness: 20 * 20 * 0.5 mm, single side), and dried in an oven at 60 ° C for 12 h to obtain a gas diffusion cathode containing a catalyst layer (Ni 0.5 La 0.5 The loading capacity is 2.5 mg cm -2 ).

[0065] 3) The process and conditions are the same as steps 1) and 2) above, except that 20 mg of Ni 0.5 La 0.3 P 0.2 (Shanghai Hydron Technology Co., Ltd., particle size range 20-50nm) instead of Ni 0.5 La 0.5 , the rest remain unchanged, and a powder gas diffusion anode is prepared, (where Ni 0.5 La 0.3 P 0.2 The loading capacity of the powder was 2.5 mg cm -2 )

[0066] In the electrolytic cell, the electrolytic cell structure and test device refer to Figure 1 and Figure 2 The anode uses IrO2 as the active ingredient (Shanghai Hydrogen Luan Technology Co., Ltd., model: PHOENIX-IrO2-1, particle size <50nm), and the cathode uses the Ni prepared above. 0.5 La 0.5 Gas diffusion anode, produced by Dioxide Materials X37-50GradeRT was used as the separator between the cathode and cathode, 1M KOH was used as the electrolyte, and the circulation flow rate was 20 mL min -1 , the temperature is 80℃, the cathode and anode are circulated on both sides, and the polarization curve is tested in the voltage range of 0-2.0V using a DC power supply. Figure 3 is the current density of hydrogen production by water electrolysis of the gas diffusion anode prepared in this embodiment. Figure 3 It can be seen that using Ni 0.5 La 0.5 The current density of water electrolysis for hydrogen production using a gas diffusion cathode can reach up to 2 V @ 1.2 A cm -2 , which is higher than the current density of 2V@1.0A cm using Pt / C (Shanghai Hydron Technology Co., Ltd., model: PHOENIX-40Pt / C-1) as the cathode.-2 , and also higher than Ni 0.5 La 0.3 P 0.2 2V@0.8A cm at cathode -2 , showing significant advantages.

[0067] Example 2

[0068] A gas diffusion cathode for anion membrane water electrolysis to produce hydrogen and a preparation method thereof, the steps are as follows:

[0069] 1) 83 mg Ni 0.75 Co 0.25 Alloy (Shanghai Hydron Technology Co., Ltd., NiCo, alloy particle size: 20-150nm, the following table represents the atomic number ratio of the corresponding metal in the alloy, with the total number of atoms in the alloy as 1), 83mg graphene (powder particle size <50nm) and 382mg polyvinylidene fluoride (5wt%) are uniformly mixed, polyvinylidene fluoride accounts for 1% of Ni 0.75 Co 0.25 10.3% of the total mass of the alloy, graphene and polyvinylidene fluoride, 350 mg of anhydrous ethanol was added to the solid powder mixture, and ultrasonic stirring was carried out at room temperature for 30 minutes to obtain a uniform catalyst layer slurry.

[0070] 2) The above catalyst layer slurry was sprayed onto one side of a carbon cloth (Shanghai Hydrogen Luan Technology Co., Ltd., PHOENIX-05CC, single side) with a length*width*thickness=40*40*0.5 mm using an electrostatic sprayer at a deposition rate of 2 mL min -1 , effective area is 16cm 2 The gas diffusion cathode containing the catalyst layer (Ni 0.75 Co 0.25 The alloy loading is 4 mg cm -2 ).

[0071] In the electrolytic cell, the electrolytic cell structure and test device refer to Figure 1 and Figure 2 The anode uses IrO2 as the active ingredient (Shanghai Hydrogen Luan Technology Co., Ltd., model: PHOENIX-IrO2-1, particle size <50nm), and the cathode uses the Ni prepared above. 0.75 La 0.25 Gas diffusion anode, electrolyte is 1M KOH, circulation flow rate is 30mL min -1 , the temperature is 80℃, the anode and cathode are circulated on both sides, and the FAAM-3-20um membrane of fumatech is used as the anode and cathode separator.

[0072] like Figure 3As shown, the Ni prepared in this embodiment 0.75 Al 0.25 The reaction current density of the alloy gas diffusion anode in 1MKOH solution water electrolysis can reach 2V@1.6Acm -2 , higher than 2V@1.0Acm in the same Pt / C cathode pure water system -2 .

[0073] Example 3

[0074] A gas diffusion cathode for anion membrane water electrolysis to produce hydrogen and a preparation method thereof, the steps are as follows:

[0075] 1) 2 mg Ni 0.4 Fe 0.4 Co 0.2 Alloy and 2mg Ni 0.8 Al 0.2 powder (Shanghai Hydrogen Technology Co., Ltd., NiFeCo, particle size: 30-200nm; Shanghai Hydrogen Technology Co., Ltd., NiAl, particle size, <50nm; the following table represents the atomic number ratio of the corresponding metal in the alloy, with the total number of atoms in the alloy as 1), 6mg multi-walled carbon nanotube powder (powder particle size <50nm) and 80mg perfluorosulfonic acid emulsion (5wt%), perfluorosulfonic acid emulsion accounts for Ni 0.4 Fe 0.4 Co 0.2 Alloy, Ni 0.8 Al 0.2 The powder and 28.5% of the total mass of perfluorosulfonic acid were uniformly mixed, and then 3.6 mg of anhydrous ethanol was added to the solid powder mixture, and ultrasonic stirring was performed at room temperature for 60 minutes to obtain a catalyst layer slurry.

[0076] 2) The above catalyst layer slurry was printed onto the nickel foam by screen printing, with an effective area of ​​length * width * thickness = 15 * 15 * 0.2 mm (single-side coating). Drying was carried out in an oven at 60°C for 3 h to obtain a gas diffusion cathode containing a catalyst layer (wherein the catalyst loading was 1 mg cm -2 ).

[0077] In the electrolytic cell, the electrolytic cell structure and test device refer to Figure 1 and Figure 2 The anode used an anode with IrO2 as the active ingredient (Shanghai Hydrogen Luan Technology Co., Ltd., model: PHOENIX-IrO2-1, particle size <50nm), the cathode used the gas diffusion anode prepared above, the electrolyte used 1M KOH, and the circulation flow rate was 10mL min -1 , the temperature is 80℃, the anode is circulated on one side, and the two electrodes are separated by an anion exchange membrane (PHOENIX-30um) produced by Shanghai Hydrogen Luan Technology Co., Ltd.

[0078] like Figure 3 As shown, the reaction current density of the gas diffusion anode prepared in this embodiment in the electrolysis of 1M KOH solution can reach 2V@1.5A cm -2 , higher than 2V@1.0Acm in the similar Pt / C cathode system -2 .

[0079] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A gas diffusion cathode comprising a substrate and a catalyst layer attached to one or both surfaces of the substrate, characterized in that: The catalytic layer includes catalytically active components, a conductive agent, and a binder; The mass ratio of the catalytically active component to the conductive agent is 1:7 to 7:1 (preferably 1:5 to 3:1, more preferably 1:2 to 1:5); The mass of the binder is 10% to 40% (preferably 12% to 38%, more preferably 15% to 30%) of the total mass of the catalyst layer; The catalytically active component is selected from at least one or more of nickel-based non-noble metal alloys or their derivatives.

2. The gas diffusion cathode according to claim 1, characterized in that: The nickel-based non-precious metal powder and alloy are selected from one or more elements such as NixMy (M=Fe, Co, Al, Cr, Mo, Mg, Mn, Zn, Sn, La, Cu, FeCo, MoCo, one or more thereof, x=0.2-0.9 (preferably 0.25-0.85, more preferably 0.50-0.70), y=0.8-0.1 (preferably 0.75-0.15, more preferably 0.40-0.20)) (x and y respectively represent the atomic number ratio of their corresponding metals in the alloy, with the number of atoms in the alloy being 1).

3. The gas diffusion cathode according to claim 1, characterized in that: The conductive agent is selected from one or more of carbon powder, carbon nanotubes, carbon nanofibers, graphene, and nanographite powder.

4. The gas diffusion cathode according to claim 1, characterized in that: The binder is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride or perfluorosulfonic acid resin.

5. The non-precious metal gas diffusion cathode according to claim 1, characterized in that: The substrate is a conductive porous substrate, which can be one or more of carbon paper, carbon cloth, porous titanium, foamed nickel, foamed zinc, foamed nickel iron, etc., or one or more of the composite structures obtained by adding a surface smoothing layer.

6. The gas diffusion cathode according to claim 1 or 5, characterized in that: The gas diffusion anode has a catalytically active component loading of 1 mg cm -2 ~8mg cm -2 The preferred loading amount of the catalytically active component is 1 mg cm -2 ~4mg cm -2 .

7. A method for preparing a gas diffusion cathode according to any one of claims 1 to 6, characterized in that: The following steps are involved: a) mixing a catalytically active component, a conductive agent and a binder to obtain a solid powder mixture; b) adding a dispersant to the solid powder mixture to obtain a catalyst layer slurry; c) coating the catalyst layer slurry onto a substrate and drying the catalytic layer.

8. The preparation method according to claim 7, characterized in that: In step b), the mass ratio of the solid powder mixture to the dispersant is 1:1 to 200:1 (preferably 1:5 to 1:200, more preferably 1:50 to 1:100); the dispersant is selected from one or more of ultrapure water, anhydrous ethanol, isopropanol or n-butanol; In step c), the coating method is selected from any one of electrodeposition, direct deposition, air spraying, electrostatic spraying, ultrasonic spraying, sputtering, doctor blade coating, screen printing, and roller pressing; Drying temperature is 30-90℃ and time is 2-8h.

9. A gas diffusion cathode for anion exchange membrane water electrolysis to produce hydrogen, characterized in that: It comprises a hydrophobicized conductive porous substrate and the catalytic layer as claimed in claim 1.

10. Use of the gas diffusion cathode according to any one of claims 1 to 6 as a cathode in an anion exchange membrane water electrolysis hydrogen production or an anion exchange membrane water electrolysis electrochemical oxidation reactor.

Citation Information

Patent Citations

  • Bifunctional electrocatalytic material and preparation method and application thereof

    CN111672514A

  • Gas diffusion electrode for preparing carbon monoxide by electrolyzing carbon dioxide and preparation method of gas diffusion electrode

    CN113445064A

  • Gas diffusion layer for anion exchange membrane electrolysis and method for producing same

    CN118355149A

  • Prestressing Steel ancher nail method

    KR1020210056292A

  • Portable cleaning pouch

    KR102165924B1

Cited By

  • Anion exchange membrane electrolyzed water cathode electrode and preparation method thereof

    CN121852978A